Capturing the value of biosurveillance "big data" through natural capital accounting. Issue 3 (3rd July 2021) - Castle, David; Hebert, Paul D.N.; Clare, Elizabeth L.; Hogg, Ian D.; Tremblay, Crystal
ABSTRACT: Global biodiversity is in crises. Recognition of the scale and pace of biodiversity loss is leading to rapid technological development in biodiversity science to identify species, their interactions, and ecosystem dynamics. National and international policy developments to stimulate mitigation and remediation actions are escalating to meet the biodiversity crises. They can take advantage of biosurveillance "big data" as evidence for more sweeping and impactful policy measures. The critical factor is translating biosurveillance data into the value-based frameworks underpinning new policy measures. An approach to this integration process, using natural capital accounting frameworks is developed.